Does Time to Pelvic Fixation Influence Outcomes in Trauma Patients?. Issue 5 (May 2022) - Taylor, Nicholas A.; Smith, Alison A.; Marr, Alan; Stuke, Lance; Greiffenstein, Patrick; Schoen, Jonathan; Brown, Tommy; Chapman, Brett; Hunt, John P.
Background: Pelvic fractures cause significant morbidity in the trauma population. Many factors influence time to fracture fixation. No previous study has determined the optimal time window for pelvic fixation. Methods: A retrospective review of trauma patients with pelvic fractures from 2016 to 2020 was performed. Patients were stratified into EARLY and LATE groups, by time to fixation within 3 days or greater than 3 days whether from admission or from completion of a life-saving procedure. Unpaired Student's t -test and Fisher's exact test were performed with multiple linear regression for variables with P < .2 on univariate analysis. Results: 287 patients were identified with a median fixation time of 3 days. There was no significant difference in demographics, incidence of preceding life-saving procedure, angioembolization, or mechanism of injury in the 2 groups ( P > .05). Length of stay in the EARLY group was significantly reduced at 11.9 +/− .7 days compared to 18.0 +/−1.2 days in the LATE group ( P < .001). There was no significant difference in rates of ventilator-associated pneumonia, deep vein thrombosis, pulmonary embolism (PE), acute kidney injury (AKI), pressure ulcer, or acute respiratory distress syndrome (ARDS) ( P > .05). There were significantly more SSIs (surgical site infections) in the LATE group. After multiple linear regression adjusting for covariates of age and ISS, the difference in hospital LOS was 5.5 days (95% CI −8.0 to −3.1, P < .001). Discussion: Fixation of traumatic pelvic fractures within 3 days reduced LOS. Prospective multi-center studies will help identify additional factors to decrease time to surgery and improve patient outcomes.